Pocket guide to accompany emergency medical responder : EMT in action - Aehlert, Barbara. 4 0 16; Aehlert, Barbara; 5 (New York, NY : McGraw-Hill, 2009)
Topics include: advanced airway techniques; baseline vital signs and SAMPLE history; bleeding and shock; environmental emergencies; infant and child emergency care; legal and ethical issues; lifting and moving patients; patient assessment; pharmacology; poisoning and overdose; scene size-up; the well-being of the emergency medical technician.
McGraw-Hill higher education.;Includes index.
Keywords: 2 -- 0; 6; Emergency medicine;Emergency medical technicians;Emergency Medical Services;Emergency Medical Technicians -- 20 -- Study guides.;Study guides.;Handbook.;Handbook.; 20; 2